2013
DOI: 10.1097/aln.0b013e31829761c8
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based Assessment and Retraining for the Anesthesiologist Seeking Reentry to Clinical Practice

Abstract: Anesthesiologists seeking to return to active clinical status are a heterogeneous group. The simulated environment provides an effective means by which to assess baseline competency and also a way to retrain physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…While simulation assessment for physicians remains controversial,42 it is currently the only way to “show how”, especially for management of unpredictable rare clinical crises. Simulation might be an effective tool to assess competency and (re)train anesthesiologists who are seeking active clinical status 43. These physicians are a heterogeneous group and not always elderly.…”
Section: Assessment Of Physicians For Age-related Decline In Competencementioning
confidence: 99%
“…While simulation assessment for physicians remains controversial,42 it is currently the only way to “show how”, especially for management of unpredictable rare clinical crises. Simulation might be an effective tool to assess competency and (re)train anesthesiologists who are seeking active clinical status 43. These physicians are a heterogeneous group and not always elderly.…”
Section: Assessment Of Physicians For Age-related Decline In Competencementioning
confidence: 99%
“…For example, the American Heart Association currently uses simulated experiences for nurse anesthetists, as well as other health care workers, in the high-stakes certification process for Advanced Cardiac Life Support, Basic Life Support, and Pediatric Advanced Life Support (American Heart Association, 2017). Additionally, high-fidelity simulation has been found to provide an effective means to evaluate competency and retrain anesthesiologists seeking reentry to practice (DeMaria, Samuelson, Schwartz, Sim, & Levine, 2013). The panel's unanimous agreement on question 14, noting the simulation's ability to provide an acceptable substitute to clinical practice for assessing provider competency, certainly favors the use of high-fidelity patient simulation for high-stakes assessment.…”
Section: Aim 2: the Use Of Simulation For High-stakes Assessmentmentioning
confidence: 99%
“…23 For example, Demaria and colleagues found that a program, aimed at anesthesiologists returning to work, consisting of a two-day simulation-based session provided an effective assessment and retraining tool. 24 Simulation has also been proven as a technique for improving technical skills and reducing cost in a variety of medical areas, including bedside procedures, and can be employed to retrain attendings. 2,25 Retraining opportunities may be organized among faculty only, in conjunction with residents, or in conjunction with other interprofessional team members learning similar skills.…”
Section: Future Directionsmentioning
confidence: 99%